Geologi Batuan Dasar Gunung Ciremai Jawa barat - Samodra, Hanang (Perhimpunan Biologi Indonesia, 2008)
ABSTRACTThe Stone Geology Structure of Ciremai Mountain West Jawa. A Middle to LateMiocene rocks association around the Ceremai Volcano, namely the Cinambo, Cantayanand Bantarujeg Formations is a deep marine sediment that physiographically belongs tothe Bogor Zone. As a submarine fan system, this turbidite sediment has already progradedto the north. The provenance of sediments is a landmass that occupied the southern partof the deep basin. Shallowing of the basin during Late Tertiary is roled by Plioceneclaystone forming of the Subang, Kaliwangu and Citalang Formations. The claystonewas deposited in a middle neritic to fluviatile environment. During the early Quaternarytime the deep basin has totally become a landmass and the building of Ceremai Volcanowas started. The difference kind of rocks will influence chemical composition of soil,and the diversity of vegetation is possibly implied by this phenomenon.Key words: stone. structure, geology, ciremai